Relationship between Anxiety as a State and Anxiety as a Trait in High School Students in Montería, Colombia: A Correlational Analysis - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study aims to analyze the relationship between state anxiety (AXE) and trait anxiety (AXR) in a sample of 160 secondary school students from the city of Montería, Colombia, using a simple linear regression econometric model. A quantitative correlational design was employed to determine the magnitude and significance of the relationship between both variables. The correlation matrix revealed a coefficient of r = -0.0196, indicating an extremely weak negative relationship. The simple linear regression models presented a regression coefficient of -0.01961 with a p-value of 0.793 and a determination coefficient (R²) of 0.00038, suggesting that state anxiety is not a significant predictor of trait anxiety and vice versa. These findings reflect a nearly null correlation and a non-explanatory model. Theoretical implications suggest that both dimensions of anxiety may occur independently or be influenced by non-linear patterns, emphasizing the need for more complex methodological approaches in future research conducted in similar school contexts.